Some aspects of examination of children with combined spine and pelvis pathology living in an industrial city - M. B. Negreyeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The aim of the study was to analyze the peculiarities of combined spinal and pelvic pathology in children living on the industrial area of the Irkutsk Region. To perform the analysis we carried out the clinical-roentgenological research, and when making orthopedic examination we took into consideration ecological factors and used the chart of multivariative analysis. It was found that in the structure of combined pathology, pelvis asymmetry ranks first, scoliosis ranks second, Legg - Calve - Perthes disease ranks third. According to the assessment of age structure of combined pathology we can conclude that at the equal manifestations of scoliosis, Spina bifida, retrospondylolisthesis, pelvis asymmetry, children of 11-15 y.o. more often have Legg - Calve - Perthes disease, children of 16-21 y.o. - coxarthrosis. In its turn relative share of Legg - Calve - Perthes disease cases in children living within a radius of 5 km from the industrial center is the largest (21 из 28 cases). It's important to mention that Legg - Calve - Perthes disease was registered in all examined boys and only in 35.5 % of girls. I and II degrees of manifestation of clinicoroentgenologic disorders of combined spine and pelvis pathology prevail (77 and 43 cases correspondingly) over the disorders of the III degree (15 cases).